Akhlak kepada Diri Sendiri - Farida Fajri, Aflah Fatkhurrokhim (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
Morals towards oneself reflect how a person treats himself personally, both in relation to physical, emotional, and ethical values. This is very important for creating balance, happiness, and well-being in one's life. This research aims to explore the concept of morals towards oneself and its implications in everyday life. Morals towards oneself are attitudes, actions and understanding that involve good and wise treatment of oneself, including physical, emotional and spiritual care. This research method is a library research where this method involves in-depth literature analysis about the concept of morals from an Islamic perspective. This research explores the concept of morals towards oneself in Islam, which emphasizes the importance of maintaining a balance between physical and spiritual needs, and avoiding behavior that is detrimental to oneself. The results of this research indicate that morals towards oneself involve developing deep self-awareness, good self-regulation, and maintaining physical and mental health. The implication of this research is the importance of understanding and practicing morals towards oneself as a foundation for achieving holistic happiness and well-being.